Efecto de la sombra de 5 materiales genéticos de Eucalyptus sp en la oferta forrajera de una pastura base de agropiro en el norte de la provincia de Buenos Aires - Martín, Alejandro (2023)
In the north of the Buenos Aires province, Eucalyptus stands began to be incorporated into cattle lots, transforming them into mixed production systems. The production of the forage component in autumn and the photosynthetically active radiation (RFA) transmitted under the canopy of different commercial genetic materials of Eucalyptus sp. were evaluated. The INTA GC27 clone differed significantly from the H105 clone in biomass production and transmitted radiation. The reduction in pasture yield with respect to the controls was between 11.9% for clone INTA GC27 and 27.9% in the case of H105. These results are preliminary and need to be confirmed in subsequent studies.